Roles of money, media and political machinery reconsidered : The Malaysian 12th general election 2008 / Nursuria Mahrif, dan Sharon Pearl Henry Serub - Mahrif, Nursuria; Henry Serub, Nursuria Mahrif, dan Sharon Pearl (2008)
Among the important requisites for democracy is the freedom of the media as well as freedom to form and organize political parties. And to make possible the workings of democracy is having regular election, meaning political parties must be allowed to campaign, and hence enabling them to present their manifesto to the electorates to vote for those who they wish to govern over them. For this process to run smoothly, money is an essential element; a tool for the running of the election process itself as well as to enable the various political parties to organize their campaign. Thus in any election, these three elements of money, media and political machinery must come into play to enable the selection and later, formation of the government to be done. This paper will discuss the roles of these three elements in the 12'h General Election 2008